2008
DOI: 10.1093/rheumatology/ken370
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of scleroderma lesional skin reveals activated wound healing phenotype of epidermal cell layer

Abstract: Consistent with previous models of SSc pathogenesis these data are showing increased contractility, increased extracellular matrix and response to oxidative stress in the involved skin of recent onset SSc patients. In addition, we show that SSc epidermis has an activated, wound healing phenotype. These findings are important because epidermal cells activated by injury induce and regulate local fibroblasts during wound repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 42 publications
9
53
0
Order By: Relevance
“…In some diseased states such as in psoriasis where the epithelial cells undergo hyperproliferation and/or aberrant differentiation, expression of keratins K6 and its partner K16 are induced in the inter-follicular epidermis (Bernot et al, 2002). Recent, proteomic analysis of whole skin lesions from SSc patients shows abnormal expression of K6 and K16 suggesting hyperproliferation of the epidermal component in SSc (Aden et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In some diseased states such as in psoriasis where the epithelial cells undergo hyperproliferation and/or aberrant differentiation, expression of keratins K6 and its partner K16 are induced in the inter-follicular epidermis (Bernot et al, 2002). Recent, proteomic analysis of whole skin lesions from SSc patients shows abnormal expression of K6 and K16 suggesting hyperproliferation of the epidermal component in SSc (Aden et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, immunohistochemical validation of these data showed that the cells responsible for the increased gene expression are keratinocytes from the basal layer of the epidermis, presenting a new and challenging concept in SSc pathophysiology. Indeed, the notion of epithelial cells playing a crucial role in the pathogenesis of skin fibrosis was more recently confirmed by another elegant proteomic study on SSc skin biopsies [18]. In fact, Aden et al [18] have shown convincing data indicating that the epithelial cells in SSc are activated and express a wound healing-like phenotype.…”
Section: Gene Expression Profiling and Molecular Subsets In Systemic mentioning
confidence: 96%
“…Indeed, the notion of epithelial cells playing a crucial role in the pathogenesis of skin fibrosis was more recently confirmed by another elegant proteomic study on SSc skin biopsies [18]. In fact, Aden et al [18] have shown convincing data indicating that the epithelial cells in SSc are activated and express a wound healing-like phenotype.…”
Section: Gene Expression Profiling and Molecular Subsets In Systemic mentioning
confidence: 96%
See 1 more Smart Citation
“…Some of the same barriers to effective application of mass spectrometry as an analytical tool (as discussed above) have impeded analysis of cell-cell and cell-matrix adhesion-dependent processes such as wound healing and cancer (14). The study of extracellular matrix (ECM) 1 and adhesion-related proteins is further complicated by the difficulty in sample preparation because compared with cytosolic proteins basal cell proteins are often highly insoluble (e.g.…”
mentioning
confidence: 99%